If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(x + 2) + ln(2x + 2) = 0 Reorder the terms: ln(2 + x) + ln(2x + 2) = 0 (2 * ln + x * ln) + ln(2x + 2) = 0 (2ln + lnx) + ln(2x + 2) = 0 Reorder the terms: 2ln + lnx + ln(2 + 2x) = 0 2ln + lnx + (2 * ln + 2x * ln) = 0 2ln + lnx + (2ln + 2lnx) = 0 Reorder the terms: 2ln + 2ln + lnx + 2lnx = 0 Combine like terms: 2ln + 2ln = 4ln 4ln + lnx + 2lnx = 0 Combine like terms: lnx + 2lnx = 3lnx 4ln + 3lnx = 0 Solving 4ln + 3lnx = 0 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'ln'. ln(4 + 3x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(4 + 3x)' equal to zero and attempt to solve: Simplifying 4 + 3x = 0 Solving 4 + 3x = 0 Move all terms containing l to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 3x = 0 + -4 3x = 0 + -4 Combine like terms: 0 + -4 = -4 3x = -4 Add '-3x' to each side of the equation. 3x + -3x = -4 + -3x Combine like terms: 3x + -3x = 0 0 = -4 + -3x Simplifying 0 = -4 + -3x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 3(v+8)-5v=14 | | 7(-3y+2)=3(8+7y) | | 6a+b=-3 | | 24-3x=9 | | (9x+7)-(3x-2)= | | 9a+3b+c=4 | | 12-10x=122-45x | | 8y+7=-6y+2 | | 10+4x=3(7x-4)+5x | | -21p^2-24p=12 | | (-x^5)(-x)= | | 10x+2=-2+4 | | 2kx*2kx=0 | | (3x+9)+(6x+7)= | | 5x+10=4x+15 | | 6x+10y+11=0 | | x^2+2kx-7=0 | | -10p+3(8+8n)=-6(n-4) | | 137-5x=-58-8x | | 5x+9=39-7x | | 3y(5y+9)=0 | | 63-6x=9+18 | | 5x-3(x-10)=100-2(3x+5) | | 2(g+6)=24 | | .83=-.4b+.33b | | 5(g+6)=24 | | 3(x^2+4x+4)=0 | | n+8m=d | | 30n=-5 | | x=42*7 | | 2x(x-1)=5(x+3) | | 2x^3-11x^2+22x-15=0 |